DAMPAK SOSIAL PENAMBANGAN EMAS TANPA IZIN DI DESA KASANG LIMAU SUNDAI KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Entika, Windy; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted in Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency. The purpose of this study is to explain the impact of singingi kuantan gold mining and explain the government's efforts to counter illegal gold mining. The research subjects involved in this study were 1 village head, 1 custom shop, 2 miners, 4 community members in Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency. This research use desciptive qualitative approach. The method used is observation, documentation and in-depth interviews. Checking data from various sources is carried out through technical triangulation as an effort to increase the researcher's understanding of what has been found. From the results of the research conducted, it shows that the Socio-Economic Impact has increased on the economy of the mining community, reduced responsiveness, and can open other business sources, namely rice stalls, mining equipment stalls and increased the income of traders in Kasang Limau Sundai Village. Social Ecological Impacts, namely river water becomes turbid, river water cannot be used anymore as a source of clean water, used crates can no longer be used properly because they leave voids and puddles, river bank abrasion occurs, river water cannot be used for aquaculture.. The government has made efforts to stop PETI but cannot stop it completely because the efforts made have not discouraged the PETI perpetrators. Keywords: Social Impact, Unlicensed Gold Mining, Socioeconomic impact